2017
DOI: 10.1111/jvs.12526
|View full text |Cite
|
Sign up to set email alerts
|

Ungulate grazing drives higher ramet turnover in sodium‐adapted Serengeti grasses

Abstract: Questions: Ungulate grazers requiring sodium (Na) will preferentially graze in areas with Na-accumulating forage grasses (i.e. many saline soils with high NaCl). Given that high-Na conditions necessitate specific adaptations in plants, the mechanisms allowing plants to persist under combined herbivory and Na stress are unclear. Has adaptation to soil salinity in East African grasses modified the evolution of grazing tolerance, leading to plants that are susceptible to defoliation? Does grazing differentially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…By contrast, we found that the C 4 LFTs had higher SLA than the C 3 LFT, but SLA did not differ between the two dominant C 4 grass lineages (Atkinson et al ., 2016). SLA can be highly variable within lineages in grasses, probably due to the importance of herbivore pressure as a competing demand on leaf economics (Anderson et al ., 2011; Griffith et al ., 2017b) as well as intraspecific variation. As a result, SLA highlighted that some traits are harder to generalise than others using the LFT approach and suggested that a range of values may be more appropriate than a single value for constraining LFT parameters.…”
Section: Lfts For Grasses Differ Drastically In Key Functional Traitsmentioning
confidence: 99%
“…By contrast, we found that the C 4 LFTs had higher SLA than the C 3 LFT, but SLA did not differ between the two dominant C 4 grass lineages (Atkinson et al ., 2016). SLA can be highly variable within lineages in grasses, probably due to the importance of herbivore pressure as a competing demand on leaf economics (Anderson et al ., 2011; Griffith et al ., 2017b) as well as intraspecific variation. As a result, SLA highlighted that some traits are harder to generalise than others using the LFT approach and suggested that a range of values may be more appropriate than a single value for constraining LFT parameters.…”
Section: Lfts For Grasses Differ Drastically In Key Functional Traitsmentioning
confidence: 99%
“…The C:N ratio is a strong indicator of palatability (e.g. Griffith et al., ) and shows significantly more variation than expected by a Brownian model of trait evolution ( K = 0.62, p = 0.003), indicating that distantly related grasses have evolved similar levels of palatability. This result is unsurprising giving the high level of variation in herbivory‐related traits such as Leaf Mass per Area in these grasses (Anderson et al., ).…”
Section: Example Application Of Nirs Plant Stoichiometry Data To Ecolmentioning
confidence: 99%
“…For this analysis, above‐ground biomass samples for each species were collected from each of 10 sites (20 × 50 m plots) spanning the entire rainfall gradient in Serengeti (see Griffith, Quigley, & Anderson, and Griffith, Anderson, & Hamilton, for details of the data collection). We aggregated individual samples by species at each site because many samples had low biomass.…”
Section: Example Application Of Nirs Plant Stoichiometry Data To Ecolmentioning
confidence: 99%
“…All animals require sodium (Robbins 1994), but it is not considered an essential nutrient for plants and can be toxic at high concentrations (Kronzucker et al 2013). Because of their sodium requirements, grazers seek out plants with high sodium concentrations (Griffith et al 2017), and, consequently, by concentrating sodium in their leaves, grasses cannot only get rid of excess sodium, but promote regular grazing to maintain high light conditions close to the soil level (i.e. high sodium concentrations can facilitate the persistence of short-statured grasses in communities that might otherwise grow tall and shade them out).…”
Section: Relevant Environmental Filtersmentioning
confidence: 99%
“…high sodium concentrations can facilitate the persistence of short-statured grasses in communities that might otherwise grow tall and shade them out). Grasses with high FS concentrations should, thus, also have traits conferring high resistance or tolerance to grazing (Griffith et al 2017).…”
Section: Relevant Environmental Filtersmentioning
confidence: 99%